A novel stress response mechanism, triggered by indole, involved in quorum quenching enzyme MomL and iron-sulfur cluster in Muricauda olearia Th120 - Wang, Yan (Sci Rep, 2017)
Indole, as a signal molecule, is involved in multiple physiological behavior including biofilm formation, antibiotic resistance and virulence. In this study, we demonstrated that indole was involved in iron deficient and H(2)O(2) stress response in Muricauda olearia Th120. Transcriptome analysis showed that totally 206 genes were regulated by exogenous indole. Besides, momL-suf gene cluster, consisting of quorum quenching enzyme coding gene momL and iron-sulfur biosynthetic genes suf, were involved in indole-induced stress response pathway. The result indicated that indole not only up-regulated momL-suf gene cluster, but also enhanced the MomL secretion and the growth rates of MomL-bearing strains in H(2)O(2) stress and iron deficient culture conditions. Co-incubation of M. olearia Th120 and Pectobacterium carotovorum subsp. carotovorum under H(2)O(2) condition revealed that M. olearia Th120 bearing MomL possessed an increased competitive advantage, whereas its competitor had a reduced survival. The phenomenon that quorum quenching enzyme is triggered by stress factor has been rarely reported. The study also opens a new clue to explore the indole function towards quorum quenching factor in bacteria.